2015
DOI: 10.1585/pfr.10.3402053
|View full text |Cite
|
Sign up to set email alerts
|

Study of Nonlinear Behavior of Low-Frequency MHD Mode Caused by Transition of Radial Electric Field in LHD

Abstract: The response of low-frequency magnetic fluctuations in a transition of radial electric field (E r ) is investigated in the edge region of LHD plasmas. Consequently, the amplitude of a magnetic fluctuation with f 2 -5 kHz is suddenly enhanced at the transition timing of E r , and then disappeared after the transition of E r . Furthermore, it is found that the amplitude of H α signals is enhanced, corresponding to the abrupt diminishing of the magnetic fluctuation with f 2 -5 kHz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Using the MyView2 software, the interesting plasma physics of the LHD is investigated rapidly. From this visualized data it is found that the magnetic fluctuation with f ∼ 2-5 kHz is suddenly enhanced at the timing of the change of the poloidal rotation velocity in the last closed flux surface of the plasma [16].…”
Section: Physical Data Analysismentioning
confidence: 90%
“…Using the MyView2 software, the interesting plasma physics of the LHD is investigated rapidly. From this visualized data it is found that the magnetic fluctuation with f ∼ 2-5 kHz is suddenly enhanced at the timing of the change of the poloidal rotation velocity in the last closed flux surface of the plasma [16].…”
Section: Physical Data Analysismentioning
confidence: 90%
“…In this paper, we investigated the spatiotemporal structure of a low-frequency fluctuation in edge plasmas, which emerges at the transition of V h (which is roughly identical with the E r ) of Large Helical Device (LHD). 15 For the stellarator geometry physics, there is no large toroidal rotation because of the parallel viscosity in the toroidal direction; 16 hence, E r is mainly determined by the poloidal flow velocity V h . Furthermore, the microwave Doppler reflectometer system is the most suitable for measuring the specific local density fluctuations.…”
Section: Introductionmentioning
confidence: 99%